The advantages of using a geochemical transport model including thermodynamic equilibrium, kinetic control and surface complexation to simulate the durability of concretes exposed to chlorides and sulphates. Issue 5 (4th May 2019) - Soive, Anthony; Tran, Van-Quan; Gasc-Barbier, Muriel
Abstract: In this study, a physically and chemically based model including thermodynamic equilibrium, kinetic control and surface complexation is used. Different cases are proposed and simulated with the same set of parameters. The results are compared with experimental data. They show very good agreement between experimental and numerical results. They also show that the parameters are not very sensible to cement composition, concrete mix-design or environmental exposition. Hence, this numerical model seems to be used as a reliable tool to predict the chloride binding capability and external sulphate attack. It is also convenient because of its limited number of parameters.